FRI0306 Development of baff and icosl bispecific inhibitor amg 570 for sle treatment. (12th June 2018) - Hsu, H.; Zhang, M.; Miner, K.; Kevin, G.; Whoriskey, J.; Jacobsen, R.; Chen, C.; Ishida, K.
Abstract : Background: Systemic lupus erythematous (SLE) is a heterogeneous disease lacking highly effective treatment options. Among many cell types and pathways involved in SLE pathogenesis, aberrant B cells and T cells are critical drivers in autoantibody production and tissue damage. Autoreactive T cells drive autoreactive B cell expansion and autoantibody production. Amongst key pathways that modulate the function of these cells, inducible costimulator ligand (ICOSL) is critical for T follicular helper cell (TFH ) development and T memory cell homeostasis, while B cell activating factor (BAFF) is a critical B cell survival factor. We hypothesised that targeting both BAFF and ICOSL would be more efficacious than single BAFF or ICOSL inhibition in SLE and other autoimmune diseases. Objectives: We tested if targeting both BAFF and ICOSL has superior efficacy than single target inhibition in the mouse arthritis and lupus models. We aimed at generating BAFF and ICOSL bispecific molecule for potential treatment of autoimmune diseases such as SLE. Methods: Murine BAFF/ICOSL bispecific, combination of BAFF and ICOSL inhibitors or single inhibitor was evaluated in the sheep red blood cell (SRBC) challenge model, mouse collagen induced arthritis (CIA) model, or NZB/NZW lupus models. AMG 570 was tested for human and cyno BAFF and ICOSL binding affinities by Kinexa A. AMG 570 dual target blocking activities was evaluated in human and cyno BAFF and ICOSL mediated B cell and T cell assay, respectively. Pharmacodynamics effect of AMG 570 was evaluated in cynomolgus monkey Results: Compared to treatment with single inhibitor, combination of BAFF and ICOSL inhibitors was more effective in aemliorating arthritis incidence and severity in the mouse CIA model and NZB/NZW lupus model. The murine BAFF/ICOSL bispecific molecule inhibited murine BAFF and ICOSL mediated B and T cell bioassays, and dual target inhibition in mice. In addition, treatment with murine BAFF/ICOSL bispecific was more efficacious than single BAFF and ICOSL inhibitor in reducing anti-dsDNA IgG, delaying the onset of protenuria and improving survival in the NZB/NZW lupus model. AMG 570 was selected as the clinical candidate with high binding affinity for human BAFF and ICOSL and strong potency in the human B cell and T cell bioassays. B cell reduction was observed after AMG 570 treatment in cynomolgus monkey, consistent with the pharmacological effect of BAFF inhibition. Conclusions: Inhibition of both BAFF and ICOSL is more efficacious than single target inhibition in the mouse lupus and arthritis models. By targeting both BAFF and ICOSL, AMG 570 has the potential to achieve a large treatment effect size in autoimmune diseases such as SLE and rheumatoid arthritis. Disclosure of Interest: H. Hsu Shareholder of: Amgen, M. Zhang Shareholder of: Amgen, K. Miner Shareholder of: Amgen, G. Kevin Shareholder of: Amgen, J. Whoriskey Shareholder of: Amgen, R. Jacobsen Shareholder of: Amgen, C. Chen Shareholder of: Amgen, K. Ishida Shareholder of: Amgen